Critical Pedagogy, Discourse Tensions, and the Basic Writing Classroom: A Critical Action Research Study - Alfred A.Z. Siha (Adult Education Research Conference, 2014)
This paper discusses a critical action research study in a basic writing classroom, which made use of critical pedagogy as its theoretical framework, as it relates to one of the findings in relation to fostering writing competency and critical consciousness.